Age-Related Differences in Neural Correlates of Face Recognition During the Toddler and Preschool Years - Carver, Leslie J. (2003)
Research on the development of face recognition in infancy has shown that infants respond to faces as if they are special and recognize familiar faces early in development. Infants also show recognition and differential attachment to familiar people very early in development. We tested the hypothesis that infants’ responses to familiar and unfamiliar faces differ at different ages. Specifically, we present data showing age-related changes in infants’ brain responses to mother’s face versus a stranger’s face in children between 18 and 54 months of age. We propose that these changes are based on age-related differences in the perceived salience of the face of the primary caregiver versus strangers.